Determinan Pemanfaatan Pelayanan Prevention of Mother to Child Transmission Of HIV (PMTCT) di Puskemas Biak Kota - Ingrit Rita Uli Manik (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Human Immunodeficiency Virus (HIV) is the virus that causes Acquired Immune Deficiency Syndrome (AIDS). One of the efforts to prevent HIV transmission from mother to child is through the Prevention of Mother-to-Child Transmission (PMTCT) services. This study aims to analyze the factors affecting the utilization of PMTCT services by pregnant women at the Biak Kota Health Center, Biak Numfor Regency. The study design is a cross-sectional study with a quantitative approach. The sample consisted of 80 pregnant women who attended pregnancy check-ups and were selected using purposive sampling. The main instrument used was a structured questionnaire. The analysis results show a significant relationship between parity (the number of previous births) and the utilization of PMTCT services (p=0.007). The exposure to information about PMTCT also showed a significant relationship (p=0.000). Multivariate analysis indicated that the exposure to information variable was the most dominant factor influencing the utilization of PMTCT services. The higher the level of exposure to information about the PMTCT program, the greater the likelihood that pregnant women will utilize the service. This highlights the importance of effective information dissemination to increase pregnant women's knowledge and awareness in preventing HIV transmission from mother to child.